2013
DOI: 10.1111/are.12360
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 17 α-methyl testosterone and letrozole on sex reversal of protogynous grouper,Epinephelus tauvina(Forskal, 1775) and spawning performance of sex-reversed males

Abstract: This study aimed to test the efficacy of 17 amethyl testosterone (17 a-MT) alone and in combination with letrozole, an aromatase inhibitor, for the induction of sex reversal in protogynous greasy grouper, Epinephelus tauvina. Further, the long-lasting effects of these treatments and spawning performance of sex-reversed males were also investigated. Greasy grouper with oocytes in the perinucleolus stage were implanted with 5 mg 17 a-MT kg À1 body weight (T 1 ), 5 mg 17 a-MT and 0.2 mg letrozole kg À1 body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Similarly, Ranjan et al. () had reported that female fish were converted to male after 2 months of implantation of letrozole and 17 α‐MT in greasy grouper. It is understood that treatment with 17 α‐MT probably increases the androgen level in the blood; however, 17 α‐MT can be converted to oestrogen by P450 aromatase, which may also increase the oestrogen level (Kwon, McAndrew & Penman, ).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, Ranjan et al. () had reported that female fish were converted to male after 2 months of implantation of letrozole and 17 α‐MT in greasy grouper. It is understood that treatment with 17 α‐MT probably increases the androgen level in the blood; however, 17 α‐MT can be converted to oestrogen by P450 aromatase, which may also increase the oestrogen level (Kwon, McAndrew & Penman, ).…”
Section: Resultsmentioning
confidence: 88%
“…Thus, after 15 days of stocking, a total of 15 fish were randomly selected for sex reversal from female to male and were implanted with a combination of 17 α methyl testosterone (MT) and letrozole at the rate of 5 mg and 0.2 mg/kg body weight respectively. The dosage of hormone and enzyme selected and the procedure for pellet preparation and implantation were based on our earlier work (Ranjan et al., ). The remaining 15 fish were left without any implantation for development of female brooders.…”
Section: Methodsmentioning
confidence: 99%
“…and Nile tilapia (Kwon, McAndrew, & Penman, 2002;Ranjan et al, 2015). These studies indicated that increasing E2 might be due to aromatization of 17α-MT to estrogen by P450 aromatase.…”
Section: Discussionmentioning
confidence: 84%
“…Changes in growth hormone (GH) and tetraiodothyronine (T4) can reflect the growth status and testosterone (T) while estradiol can reflect the gonadal development status of fish (Power et al, 2001;Ranjan et al, 2015). Hence, comprehensive understanding of oxidation-reduction-related enzymes and growth and reproduction-related hormones is essential for evaluating the effects of exogenous 17α-MT on topmouth culter.…”
mentioning
confidence: 99%
“…The white grouper ( Epinephelus aeneus ) in the Mediterranean Sea region is not an exception and are threatened by an increasing consumer demand. In Southeast Asia, grouper culture has been implemented and is taking advantage of the species of grouper that have rapid growth, disease resistant and efficient feed conversion (Ranjan et al, ). Decreasing amounts of wild fish and bans on the fishing of groupers in the Mediterranean region prompted studies targeting culture of native grouper species, such as the white grouper.…”
Section: Introductionmentioning
confidence: 99%